World Medical Association Declaration of Helsinki: Ethical Principles for Medical Research Involving Human Subjects - Not Available (JAMA : the journal of the American Medical Association, 2000)
The 32 ethical principles of the World Medical Association's Declaration of Helsinki are presented. The principles are designed to provide guidance to physicians and other participants in medical research involving human subjects.